Cancer incidence among waiters: 45 years of follow-up in five Nordic countries. Issue 2 (March 2015) - Reijula, Jere; Kjaerheim, Kristina; Lynge, Elsebeth; Martinsen, Jan I.; Reijula, Kari; Sparén, Pär; Tryggvadottir, Laufey; Weiderpass, Elisabete; Pukkala, Eero
Aims: To study cancer risk patterns among waiters in the Nordic countries. Methods: We identified a cohort of 16, 134 male and 81, 838 female waiters from Denmark, Finland, Iceland, Norway and Sweden. During the follow-up period from 1961 to 2005, we found that 19, 388 incident cancer cases were diagnosed. Standardised incidence ratio (SIR) was defined as the observed number of cancer cases divided by the expected number, based on national age, time period and gender-specific cancer incidence rates in the general population. Results: The SIR of all cancers in waiters, in the five countries combined, was 1.46 (95% CI 1.41–1.51) in men and 1.09 (1.07–1.11) in women. In male waiters, the SIR decreased from 1.79 (1.63–1.96) in 1961–1975, to 1.33 (1.26–1.40) in 1991–2005, but remained stable among women. The SIR among male waiters was highest for cancers in the pharynx (6.11; 95% CI 5.02–7.37), oral cavity (4.91; 95% CI 3.81–6.24) and tongue (4.36; 95% CI 3.13–5.92); and in female waiters, in the larynx (2.17; 95% CI 1.63–2.82), oral cavity (1.96; 95% CI 1.60–2.34) and lung (1.89; 95% CI 1.80–1.99). Conclusions: The risk of cancer among waiters was higher than in the general population. The elevated incidence in some cancer sites can likely be explained by higher alcohol consumption, the prevalence of smoking and occupational exposure to tobacco smoke. Hopefully, the incidence of cancer among waiters will decrease in the future, due to the banning of tobacco smoking in restaurants and bars in the Nordic countries.